The Poor Sanitation and Access to Clean Water in Rural Areas: Case of Bossangoa (Central African Republic) - Kamba, Francklin; Sangija, Frank; Wei, Shiqiang (Advances in Social Sciences Research Journal, 2016)
Inadequate access to water services and sanitation associated with poor hygiene practices continues to kill millions of people in rural areas of developing countries especially in Africa. Access to safe drinking water has a great influence on health, economy and good life of the people. This paper is a case study of the poor sanitation and access to clean water in a rural area of Bossangoa district in Central African Republic. The research had three broad objectives: to assess the relevant literature on water sanitation and health, assess water sanitation and health condition in Bossangoa area, and provide the public with information on good practices of water supply and sanitation for sustainable and environmental management. To achieve these objectives, the study combined several methodological approaches. An experimental approach was to visit and observe all supply water points. Quantitative household survey and a qualitative approach by organizing group discussions for data collection were also used. The data were processed using Excel and analyzed with descriptive statistics. It is clear from the analysis that: despite the existence of traditional wells and boreholes, people adopt practices that affect the quality of drinking water. Their social and economic situations lead to alternate different types of water, most of which are polluted by solid and liquid waste; and the consumption of untreated water is the source of waterborne diseases in the city and its municipalities. We suggest that the government and other stakeholders should intervene in provision of safe drinking water by educating people, eradicating poverty and improving water sources.